2015
DOI: 10.1186/s12885-015-1078-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma cells alter the senescence phenotype of bone marrow mesenchymal stromal cells under participation of the DLK1-DIO3 genomic region

Abstract: BackgroundAlterations and senescence in bone marrow mesenchymal stromal cells of multiple myeloma patients (MM-BMMSCs) have become an important research focus. However the role of senescence in the pathophysiology of MM is not clear.MethodsCorrelation between senescence, cell cycle and microRNA expression of MM-BMMSCs (n = 89) was analyzed. Gene expression analysis, copy number analysis and methylation specific PCR were performed by Real-Time PCR. Furthermore, cyclin E1, cyclin D1, p16 and p21 genes were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 52 publications
(61 reference statements)
3
38
0
Order By: Relevance
“…Previous studies have shown MIR-199b-3p and MIR-125a-3p are major negative regulators of cell migration in cancer models [23,24]. Further studies are warranted to elucidate the function of the microRNAs in the signaling cascade we present and to prove their regulatory role in our model (16). This is compatible with our observation of increased MMcond-MSCs migration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have shown MIR-199b-3p and MIR-125a-3p are major negative regulators of cell migration in cancer models [23,24]. Further studies are warranted to elucidate the function of the microRNAs in the signaling cascade we present and to prove their regulatory role in our model (16). This is compatible with our observation of increased MMcond-MSCs migration.…”
Section: Discussionsupporting
confidence: 90%
“…Cells were lysed, proteins were extracted, and the Western blot test was preformed, as described elsewhere [16]. The following proteins were detected using rabbit/mouse anti-human: peIF4E (Ser-209)/total eIF4E, peIF4GI(Ser-1108)/total eIF4GI, p4EBP(Ser-65)/total 4EBP, p-mTOR(Ser-2448)/total mTOR, p-MNK (Thr-197/Thr-202)/total MNK (Cell Signaling Technology, Danvers, MA, USA); and tubulin (Sigma-Aldrich).…”
Section: Western Blottingmentioning
confidence: 99%
“…In a study of cervical cancer, miR-519d was found to be significantly upregulated in cervical cancer samples, where it promoted the migration and invasion of HeLa and SiHa cervical cancer cells and the proliferation of cervical cancer cells through targeting Smad 7 [33]. miR-519d is also overexpressed in bone marrow mesenchymal stromal cells of multiple myeloma patients compared to bone marrow mesenchymal stromal cells of donors [34]. …”
Section: The Expression and Function Of Mir-519d In Non-placental Tismentioning
confidence: 99%
“…In contrast, K562 cells did not induce a significant down‐regulation of miR‐223 possibly accounting for a specific impact of MM cells on MM‐BMMSCs. The counteracting of MM cells on aberrations in MM‐BMMSCs compared to HD‐BMMSCs indicates the excitatory effect of MM cells on MM‐BMMSCs . Overexpression of miR‐223 in MM‐BMMSCs compared to HD‐BMMSCs could result from a senescence‐like state induced by increased activation of stromal cells by MM cells.…”
Section: Discussionmentioning
confidence: 99%